2017
DOI: 10.3389/fimmu.2017.01075
|View full text |Cite
|
Sign up to set email alerts
|

The Toll for Trafficking: Toll-Like Receptor 7 Delivery to the Endosome

Abstract: Toll-like receptor (TLR)-7 is an endosomal innate immune sensor capable of detecting single-stranded ribonucleic acid. TLR7-mediated induction of type I interferon and other inflammatory cytokine production is important in antiviral immune responses. Furthermore, altered TLR7 expression levels are implicated in various autoimmune disorders, indicating a key role for this receptor in modulating inflammation. This review is focused on the regulation of TLR7 expression and localization compared to that of the oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
111
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(114 citation statements)
references
References 127 publications
(176 reference statements)
3
111
0
Order By: Relevance
“…Following inflammatory stimuli, TLR7 is ubiquitinated and packaged into COPII-coated vesicles by the endoplasmic reticulum (ER)-resident chaperone UNC93B1 40,41 . Upon binding ssRNA, TLR7 signaling results in the production of proinflammatory cytokines and type I interferon, T-cell proliferation, and induction of T H 1 responses 42,43 . We observed many of these elements within PDAC tumors treated with R848, including CD8 + T-cell proliferation and effector function, and decreased T H 2 polarization among CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Following inflammatory stimuli, TLR7 is ubiquitinated and packaged into COPII-coated vesicles by the endoplasmic reticulum (ER)-resident chaperone UNC93B1 40,41 . Upon binding ssRNA, TLR7 signaling results in the production of proinflammatory cytokines and type I interferon, T-cell proliferation, and induction of T H 1 responses 42,43 . We observed many of these elements within PDAC tumors treated with R848, including CD8 + T-cell proliferation and effector function, and decreased T H 2 polarization among CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…The present results further suggested that TLR7 serves as a mediator of M2 macrophage polarization. In contrast to the well-known macrophage polarization-associated TLR transmembrane family members, including TLR4, TLR7 is localized in the endosomal compartment, along with TLR3/9, and is associated with the viral-induced immune response ( 46 ). A recent study demonstrated that Hepatitis C virus-induced TLR7 stimulation results in monocyte differentiation and M2 macrophage polarization ( 36 ), which is consistent with the present study and further suggests that TLR7 stimulated macrophage polarization associated with chronic liver disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…TLR7 is generally considered an antiviral molecule since it detects viral singlestranded RNA and signals for the production of type I IFNs [43]. TLR7 is expressed on macrophages, conventional dendritic cells, and plasmacytoid dendritic cells [43], and our work suggests that its presence makes these cell types more susceptible to infection with certain hMPV strains.…”
Section: Discussionmentioning
confidence: 70%
“…TLR7 is generally considered an antiviral molecule since it detects viral singlestranded RNA and signals for the production of type I IFNs [43]. TLR7 is expressed on macrophages, conventional dendritic cells, and plasmacytoid dendritic cells [43], and our work suggests that its presence makes these cell types more susceptible to infection with certain hMPV strains. Staining of primary human lung airway epithelial cells with anti-TLR7 antibodies also indicated that TLR7 is expressed on these cells [44], which are additional relevant targets of hMPV infection.…”
Section: Discussionmentioning
confidence: 70%